Work systems of persons with disabilities in the company - Imas Diana Aprilia; Prima Dea Pangestu (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
The absence of an integrative work pattern between schools, companies and the government is a major obstacle for the employment of people with disabilities. Hence, there is need to create adequate partnerships between these stakeholders in the form of systematic and integrated work system and structure. The purpose of this study is to formulate a work system of people with disabilities in the company. A qualitative approach with descriptive methods was used involving four participants, consisting of a principal and a skill teacher at a special school for deaf children, a Head of the Human Research Development (HRD) Division in a Company X, and a Head of the Department of Manpower in Bandung. Data digging is done through interviews, observation and documentation studies. The study consist of three stages, including 1) Assessment of field needs, 2) System Formulation, and 3) Execution Tests. Subsequently, the outcome is used to produce a guideline of Work System for People with Disabilities in Companies, comprising the assessment needs of Schools, Companies and the Manpower Office, alongside Work Principles and Mechanisms, as well as Evaluation. The results is the stakeholders reached an agreement on the value of meaningfulness as a guide. Effective referencing enables relevant parties to work together towards implementation, consistently in an effort to fulfill the individuals’ independence while working